The Role of IFITM Proteins in Tick-Borne Encephalitis Virus Infection - Chmielewska, Alicja M; Gómez-Herranz, Maria; Gach, Paulina; Nekulova, Marta; Bagnucka, Małgorzata A; Lipińska, Andrea D; Rychłowski, Michał; Hoffmann, Weronika; Król, Ewelina; Vojtesek, Borivoj; Sloan, Richard D; Bieńkowska-Szewczyk, Krystyna; et al. (Journal of virology, 2022)
Tick-borne encephalitis virus (TBEV), of the genus Flavivirus, is a causative agent of severe encephalitis in regions of endemicity of northern Asia and central and northern Europe. Interferon-induced transmembrane proteins (IFITMs) are restriction factors that inhibit the replication cycles of numerous viruses, including flaviviruses such as West Nile virus, dengue virus, and Zika virus. Here, we demonstrate the role of IFITM1, IFITM2, and IFITM3 in the inhibition of TBEV infection and in protection against virus-induced cell death. We show that the most significant role is that of IFITM3, including the dissection of its functional motifs by mutagenesis. Furthermore, through the use of CRISPR-Cas9-generated IFITM1/3-knockout monoclonal cell lines, we confirm the role and additive action of endogenous IFITMs in TBEV suppression. However, the results of coculture assays suggest that TBEV might partially escape interferon- and IFITM-mediated suppression during high-density coculture infection when the virus enters naive cells directly from infected donor cells. Thus, cell-to-cell spread may constitute a strategy for virus escape from innate host defenses. IMPORTANCE TBEV infection may result in encephalitis, chronic illness, or death. TBEV is endemic in northern Asia and Europe; however, due to climate change, new centers of endemicity have arisen. Although effective TBEV vaccines have been approved, vaccination coverage is low, and due to the lack of specific therapeutics, infected individuals depend on their immune responses to control the infection. IFITM proteins are components of the innate antiviral defenses that suppress cell entry of many viral pathogens. However, no studies on the role of IFITM proteins in TBEV infection have been published thus far. Understanding antiviral innate immune responses is crucial for the future development of antiviral strategies. Here, we show the important role of IFITM proteins in the inhibition of TBEV infection and virus-mediated cell death. However, our data suggest that TBEV cell-to-cell spread may be less prone to both interferon- and IFITM-mediated suppression, potentially facilitating escape from IFITM-mediated immunity.
Keywords: Cytopathogenic Effect, Viral; interakční proteinové domény a motivy; buněčné linie; flavivirus; Protein Interaction Domains and Motifs; sekvence aminokyselin; multigenová rodina; vazba proteinů; odolnost vůči nemocem; Disease Resistance; lidé; Gene Knockdown Techniques; replikace viru; interferon; membránové proteiny; viry klíšťové encefalitidy; Amino Acid Sequence; cytopatogenní efekt virový; Cell Line; TBEV; Encephalitis Viruses, Tick-Borne; Multigene Family; Disease Susceptibility; cell-to-cell spread; genový knockdown; Encephalitis, Tick-Borne; interakce hostitele a patogenu; interferony; exprese genu; Membrane Proteins; IFITM; intrinsic immunity; host factors; Host-Pathogen Interactions; klíšťová encefalitida; Virus Replication; Interferons; Protein Binding; Gene Expression; náchylnost k nemoci; Humans